Strategi Pembelajaran Pendidikan Agama Islam dalam Pembentukan Karakter Siswa di SMA Negeri 2 Badar Aceh Tenggara - Sari Pitri; Muji Mulia; Realita Realita (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
The purpose of this study was to determine the PAI learning procedure in the formation of student character, to determine the PAI learning method in the formation of student character, to determine the constraints of PAI learning in the formation of student character. . The subjects of this study were PAI teachers, totaling one person. The results that researchers got in the field, in the learning procedure there are three stages, namely preliminary activities, core activities and closing activities of the three stages, the teacher has integrated character values to students. The methods used by PAI teachers in learning are the lecture method and the question and answer method, from these methods the PAI teacher has integrated character values to students. The methods used by PAI teachers in learning are the lecture method and the question and answer method, from these methods the PAI teacher has integrated character values to students. In character building, following PAI learning procedures in general, namely initial activities, core activities and closing activities, but in these activities to integrate character values it tends to be more in core activities, where from core activities the teacher spends more time explaining the material. subject matter so that what happens is that the teacher integrates or embeds these values in core activities. The method used by the teacher in instilling character values is the right method where from the lecture method the teacher can provide character values and provide advice to students. Likewise with the question and answer method, from teacher questions and student questions, character values can be inserted to students according to the suitability of the material and these values. Teachers have obstacles in the formation of students' morals, both internally centered on the teacher himself, such as the difficulty of giving understanding to students in the subject matter because students do not focus on the explanation. then external factors, namely outside the learning process, these obstacles occur in the students' families, the lack of encouragement or motivation of parents towards children's education so that it is difficult for teachers to shape students' character.